The effect of rational choice and anti-intellectualism on students' intention to cheat. - Kuhn, Clarese (Organisational Psychology, 2024)
This study investigated the effect of rational choice and anti-intellectualism on undergraduate business students' (N = 485) intention to cheat in their academic studies. A descriptive research design was used and data was collected by means of a self-administered, cross-sectional survey. Hierarchical multiple regression analysis showed that rational choice explains a significant proportion of the variance in cheating intention over and above that of anti-intellectualism. The regression analysis also showed a significant interaction effect between anti-intellectualism and benefits of cheating. Logistic regression was used to show the strong relationship between the rational choice dimensions and self-reported cheating behaviour. Recommendations and suggestions for future research are presented.